Kekerasan Verbal dalam Wacana Politik Kudeta Partai Demokrat - Margiani Margiani (Madah: Jurnal Bahasa dan Sastra, 2022)
The background of this study is a coup attempt in Demokrat Party, which had an impact on the use of verbal violence forms. a of. This study was carried out in three stages, namely reducing data, presenting data, and drawing conclusion obtained through identification and interpretation of data. The data of this study are netizen’s utterances that contain verbal violence in the political discourse of the Democratic Party Coup. The results of this study are as follows. The netizen’s verbal violence in the Political discourse of the Democratic Party Coup can be classified into three categories, namely (1) impolite utterance (52%), (2) less polite utterance (34%), and (3) rather polite utterance (14%). The percentage result shows that although there are still some less polite and rather polite utterances, the dominant level of politeness used by netizens in the Political discourse of the Demokrat Coup is impolite.